An Intersectional Analysis of Chinese International Students’ Experiences in Post-Secondary Institutions in British Columbia - Avenido, Karlo (Journal of International Students, 2022)
Internationalization continues to be a priority of the education mandate in British Columbia (BC). While there is currently a surfeit of exploratory studies on international students’ (IS) experiences of challenges in their host institutions, little research has been done on examining their experiences from sociocultural context-based standpoints. This study fills the gap by examining the daily lived experiences of Chinese post-secondary IS in BC through the lens of intersectionality. First, the notions of cultural distance, nationality, and language proficiency were conceptualized as intersectional categories. Next, narrative data were collected from six Chinese IS, and then analyzed through an iterative coding framework that connected narrative themes to the theoretical framework of intersectionality. The results show how the interlocking categories created instances of minoritization among the participants due to power imbalances brought upon by compatriots, peers, and federal/institutional policies. Implications in future directions of intersectionality research, policy, and practices are presented.